Prevalence and risk factors for PTSD in injured workers in Bangladesh: a study of surviving workers from the Rana Plaza building collapse - T Fitch, MPH; G Villanueva, MS; M Quadir; H Alamgir, PhD (Elsevier, 2015)
Background: Bangladesh is the second largest garment-exporting country in the world, and the garment production industry is the largest manufacturing sector of its economy. Workers in this industry often have dangerous workplace conditions. As a result of a factory collapse at Rana Plaza in Savar in April, 2013, 1134 people died and about 2515 were injured. Survivors of this disaster have physical and mental health sequelae, such as post-traumatic stress disorder (PTSD). The aim of this study was to identify the prevalence of PTSD, and risk factors associated with its development, in survivors of the Rana Plaza collapse. Methods: We recruited participants using patient records from the Centre of Rehabilitation of the Paralysed (CRP) in Savar, where many workers received care after the disaster. Between April 22 and May 22, 2014, we administered the Post Traumatic Stress Disorder Checklist Specific version, and the WHO Disability Assessment Schedule (WHODAS), each of which had been translated into Bengali by CRP's research department. Local translators aided with communication and administration of the surveys and consent was obtained from the participants. Travel expenses of the participants were reimbursed. Findings: We contacted 183 patients, and all but two participated. During analysis of prevalence, χ2 test and logistical regression models were used. The prevalence of PTSD was 75·69% using the PTSD checklist list cut-off of 45. In our multivariable logistical regression, two factors were found to be significant after adjustment of confounding variables: being female (OR 1·32 [95% CI 0·36-4·85]; p=0·042), and having sustained concussion injuries (3·43 [1·15-10·27] p=0·021). In addition, WHODAS mean value for the PTSD group was 1·20 times higher than that for the non-PTSD group (1·10-1·31; p<0·0001). Psychological counselling was not significantly related to the development of PTSD. Interpretation: In Bangladesh, there are limited resources available to provide physical and mental help for injured and disabled individuals making it difficult for them to obtain the right and timely care that they need. These data could aid in early identification of people who may need additional support after workplace accidents. Finally, training for professionals in treating PTSD cases is needed. Although our results suggest that the severity of injury is related to PTSD development, longitudinal studies are needed to determine if injury severity is correlated to retention of PTSD over time. Our sample had a larger proportion of male workers than that in the injured Rana Plaza population. This finding could be because men seek out medical care more frequently or because they have a greater cultural capacity to access treatment. With most participants screening positive for PTSD, it is important to consider mental health outcomes after such disasters in developing countries. Funding: Travel expenses of participants were covered by Deutsche Gesellschaft für Internationale Zusammenarbei. Taylor Fitch and Gabriela Villanueva both received travel grants from UTHSCSA for airfare and lodging.